EPISTEMOLOGI TAFSIR Al-QUR’AN KONTEMPORER - Islah Gusmian (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2015)
This article discussed about the epistemology of thecontemporary Qur’anic interpretation. As the holy book which isshâlih likulli zaman wa makan, Qur’an would always be understoodby Muslim scholars in order to be able to find out its variousmeanings. In those processes of comprehension, human being as bothreader and interpreter has very important roles. He/she will thenformulate various methods to be able to understand practically, inorder that God’s ideas and meanings being able to be reachcomprehensively. Furthermore, this article showed that contemporaryQur’an hermeneutic, as well as formulated by Fazlur Rahman, Aminal-Khuli, Nasr Hamid Abu Zaid, be possible to be used Inunderstanding the Holy Qur’an comprehensively. Just like thehermeneutic approach from the western thinkers, such as Gadamer.